2017
DOI: 10.3892/ijo.2017.3942
|View full text |Cite
|
Sign up to set email alerts
|

High Annexin A5 expression promotes tumor progression and poor prognosis in renal cell carcinoma

Abstract: Annexin A5 has been found to act as an oncogenic protein in a variety of cancers. However, its specific biological role and mechanism in renal cell cancer (RCC) remains unknown. Quantitative Real-time PCR and western blotting were used to evaluate the mRNA and protein expression level of Annexin A5 in human RCC cell lines and tissues. Immunohistochemistry was adopted to measure the Annexin A5 expression in 123 cases of RCC tissues. Survival analysis was performed to explore the association between Annexin A5 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
3
22
1
Order By: Relevance
“…The potential of the smallest member of the annexin family as a predictive biomarker for tumor development, metastasis, and invasion has already been reviewed [ 41 ], with it also being involved in cell membrane repair [ 42 ]. Our results are consistent with reports of its overexpression in several other cancer types, including renal cell carcinoma [ 43 ], colon cancer [ 44 ], and hepatocarcinoma [ 45 , 46 ]. Other highly significant changes mainly involve two proteins, COX2 for increase and VAT1 for decrease.…”
Section: Discussionsupporting
confidence: 93%
“…The potential of the smallest member of the annexin family as a predictive biomarker for tumor development, metastasis, and invasion has already been reviewed [ 41 ], with it also being involved in cell membrane repair [ 42 ]. Our results are consistent with reports of its overexpression in several other cancer types, including renal cell carcinoma [ 43 ], colon cancer [ 44 ], and hepatocarcinoma [ 45 , 46 ]. Other highly significant changes mainly involve two proteins, COX2 for increase and VAT1 for decrease.…”
Section: Discussionsupporting
confidence: 93%
“…MMPs can promote the EMT process by cleaving, shedding, or degrading a variety of cell surface molecules (Jia et al, ). However, EMT can also be induced by proteins such as Annexin V (Tang et al, ), Snail (Zhao et al, ), or Bach 1 (Aletaha et al, ), which can regulate expression and/or activity of MMPs, thereby modulating the migratory phenotype involved in EMT.…”
Section: Functional Roles Of Mmps and Adams In The Tumor Microenvironmentioning
confidence: 99%
“…Moreover, mounting evidence has indicated AKT and its downstream molecule mTOR are involved into tumor progression by regulating MMPs family and EMT related markers [ 32 35 ]. It has been reported that AKT/mTOR signaling is activated by several tyrosine kinase receptors and exhibit great role in metabolism, proliferation, and protein synthesis in diversified tumor types [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%